(untitled) (Вісник: Міжнародні відносини, 2021)
The paper suggests retrospective analysis of investment premiums valuation models. Their place in contemporary theory of international portfolio investing is defined. Main phases of these models’ evolution are revealed, uppermost considering incorporation of local and international factors of expected returns. Basic features of these phases are discovered. Dominance of the CAPM model in the framework of expected returns valuation concept is validated. This model is underlying major part of the science in this field development, particularly zero beta model and intertemporal model. Gnoseological conditions of models including international factors of securities premiums origin and development are identified. Specific attention is paid to models considering currency risk factor – one of the key factors of expected returns in international investment environment. Major events of the world economy that actualized the necessity of considering currency risks while valuing investment premiums are singled out. International capital asset pricing model as one that incorporates currency risk factor during expected returns valuation in the best way is examined. Comparative analysis of international CAPM and the approach of using the traditional model in international market is carried out. Although no evident advantage of any is fixed, existing empirics proves that the latter is much more convenient in terms of its usage, and is actually used much more often. The rationale of methodological priority of using the term "premium" rather than "expected return" is presented. Methodological indifference between the terms "price" and "expected return" in the current context is reported.